Implementation of Science Student Work Sheet Based on Multiple Intelligence Materials Temperature and Their Changes - Maria, Maria; Silalahi, Silalahi; Aggarwal, Yashika; Galadima, Usman (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study aimed to produce multiple intelligence-based science worksheets on temperature and change material, then to determine students’ responses to science intelligence based on multiple intelligence. Methodology: The research method used is the Research and Development (R&D) method and uses the Borg and Gall development model. This study’s test subjects were Junior high school 1 Jambi City students. The research instrument was a validation questionnaire from the expert team and a student perception questionnaire. The specialist team’s validation questionnaire data analysis technique used a qualitative description. The student questionnaire data analysis technique was used using a rating scale which was then interpreted qualitatively. Main Findings: After validating the material once and validating the design three times, the Multiple Intelligences-based Science Worksheet is worth trying and gets an average percentage of student perceptions of 82% which states that this worksheet is in the "very good" category. Novelty/Originality of this study: Know the implementation of science student worksheet based on multiple intelligence materials temperature and their changes. The impact of this research is as a reference for further research to carry out further research. Then this research impacts educators and teaching staff in improving and increasing student learning literacy and learning resources.